2022
DOI: 10.1002/ejhf.2424
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological pathways related to high plasma growth differentiation factor 15 concentrations in patients with heart failure

Abstract: Elevated concentrations of growth differentiation factor 15 (GDF-15) in patients with heart failure (HF) have been consistently associated with worse clinical outcomes, but what disease mechanisms high GDF-15 concentrations represent remains unclear. Here, we aim to identify activated pathophysiological pathways related to elevated GDF-15 expression in patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…GDF signaling was specifically involved in FB subsets with DM ( Figure 6 D and Figure S6 ). GDF15 , the only ligand detected in our study, was associated with systematic inflammation, DM and obesity [ 45 , 46 , 47 , 48 ]. Our results showed that ANGPTL7 + FBs and SFRP1 + FBs expressed GDF15 and acted on a variety of cells ( Figure 6 D).…”
Section: Resultsmentioning
confidence: 99%
“…GDF signaling was specifically involved in FB subsets with DM ( Figure 6 D and Figure S6 ). GDF15 , the only ligand detected in our study, was associated with systematic inflammation, DM and obesity [ 45 , 46 , 47 , 48 ]. Our results showed that ANGPTL7 + FBs and SFRP1 + FBs expressed GDF15 and acted on a variety of cells ( Figure 6 D).…”
Section: Resultsmentioning
confidence: 99%
“… 29 As for the relationship between GDF‐15 and haemoglobin, a recently published study showed that the elevated GDF‐15 levels correlated with up‐regulation of the interleukin‐6 (IL‐6) pathway, leading to the reduction of the plasma iron levels, which then contributed to the observed decrease in the levels of haemoglobin. 30 Therefore, a high level of GDF‐15 may serve as an indicator of the risk of anaemia in patients with HF. In view of the aforementioned, GDF‐15 appears to integrate information on cardiac and extracardiac disease pathways that are related to the occurrence, progression, and prognosis of HF.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of growth differentiation factor 15 (GDF‐15) have been associated with a worse outcome. Ceelen et al 13 . measured the levels of over 300 biomarkers and analysed key biological pathways in patients divided based on GDF‐15 levels.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[10][11][12] High levels of growth differentiation factor 15 (GDF-15) have been associated with a worse outcome. Ceelen et al 13 measured the levels of over 300 biomarkers and analysed key biological pathways in patients divided based on GDF-15 levels. They found that patients with higher levels of GDF-15 had an increased activation of inflammation, as well as of pathways related to the regulation of insulin-like growth factor (IGF-1) and bone/tissue remodelling.…”
Section: Biomarkersmentioning
confidence: 99%